A cohort study of infant feeding practices in city, suburban and rural areas in Zhejiang Province, PR China - Binns Colin W; Zhao Yun; Qiu Liqian; Lee Andy H; Xie Xing (BMC, 2008)
Abstract Background Breastfeeding is the basis for appropriate nutrition for infants and is strongly supported by the Ministry of Health in China. However, there are differences in infant feeding practices in different areas of the country. The aim of this study was to compare the infant feeding practices and the prevalence of determinants of initiation and continuing to breastfeed until six months of age in city, suburb and rural areas in Zhejiang Province, PRC. Methods A longitudinal cohort study of infant feeding practices was undertaken in city, suburban and rural areas in 2004/2005. Mothers were recruited and interviewed before discharge from hospitals. A total of 1520 mothers were recruited into the study. Follow-up interviews were administered at 1, 3 and 6 months after birth to obtain details of infant feeding practices. Results 'Any breastfeeding' rates were high before discharge at all three locations, 96.5% in city, 96.8% in suburb and 97.4% in the rural area. The 'exclusive breastfeeding' rates in the city, suburban and rural areas before discharge were 38.0%, 63.4% and 61.0% respectively. By sixth months the 'any breastfeeding' rates had declined to 62.8%, 76.9% and 83.6% and the 'exclusive breastfeeding' rates had fallen to 0.2%, 0.5% and 7.2% in city, suburb and rural areas respectively. There were differences in feeding practices between the three locations, including the use of prelacteal feeds and the introduction of supplementary feeds. Conclusion Mothers who lived in the city were least likely to be 'exclusive breastfeeding' at discharge. At six months the city infants also had lower rates of 'any breastfeeding' and 'exclusive breastfeeding'.